2004
DOI: 10.1103/physrevc.69.044308
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic random-phase approximation calculation with negative energy states of nuclear polarization in muonic atoms

Abstract: We study the muonic nuclear-polarization corrections, which provide level shifts due to the two-photon exchange process between a bound muon and a nucleus. We choose 16 O as a nucleus for the demonstration of the amount and the property of the nuclear polarization in the muonic atoms. The nuclear states of 16 O are constructed in the random-phase approximation including the negative-energy states based on the relativistic mean field model. The spatial components of the transition current have large couplings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It was found that the RRPA eigenstates with negative energy have a significant role, since the transverse form factors of these states become considerably large [4]. If antinucleons are deeply bound, the transverse response function has a contribution from the antinucleon states with an energy lower than twice the nucleon mass.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the RRPA eigenstates with negative energy have a significant role, since the transverse form factors of these states become considerably large [4]. If antinucleons are deeply bound, the transverse response function has a contribution from the antinucleon states with an energy lower than twice the nucleon mass.…”
Section: Introductionmentioning
confidence: 99%
“…One should bear in mind possible complications in the special case of µ-208 Pb due to potential muonnuclear resonances; therefore, we suggest that the less intricate cases of muonic 90 Zr and 112 -124 Sn should be tackled first. The non-relativistic nuclear treatment in our calculations is justified by the excellent agreement between the non-relativistic seagull term and antinucleon NP contributions in light muonic atoms [16]. In addition, there is a general consistency between relativistic and non-relativistic approaches for a variety of nuclear phenomena [24][25][26].…”
mentioning
confidence: 64%
“…1 (b) and (c)). However, if noncommuting nuclear charge and current operators are employed, it can be shown that an additional contribution has to be included in order to ensure gauge invariance of the NP correction [15,16]. This additional term can be represented by the so-called seagull diagram (Fig.…”
mentioning
confidence: 99%
“…The present results are also consistent with the scattering analysis. In addition, it would be interesting to perform the analysis of anomaly in the nuclearpolarization corrections for the 90 Zr, 208 Pb, and Sn isotope by the present extended relativistic nuclear models; the nuclear-polarization correction is considerably sensitive to the EWSR strength and the anomaly seems to require the effective mass effect 16,17 . As regards the effect of the large effective mass, we will reconsider in the subsection of the giant quadrupole resonance.…”
Section: Ewsrmentioning
confidence: 99%